High-strength and high-conductivity glass fiber reinforced PBT composite material and preparation method thereof
By adding carbon nanostructured material CNS and dispersion additives to the PBT resin, the problems of insufficient mechanical properties and low conductivity of PBT resin are solved, and a high-strength, high-conductive PBT composite material is realized, which broadens its application range.
Patent Information
- Application Number
- CN202411962588.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
The existing PBT resin has low tensile strength, bending strength and bending modulus, which limits its application range in the industrial field. At the same time, the addition of traditional conductive fillers will affect the mechanical properties and processing properties of the material.
By adding new carbon nanostructured material CNS and suitable dispersion additives to the PBT resin, the formulation system is optimized and the dispersion of CNS in the resin is improved, thereby improving the conductive and mechanical properties of the material.
It has realized high-strength, high-conductivity glass fiber reinforced PBT composite material, which has improved the tensile strength, bending strength and bending modulus of the material, and is suitable for the automotive industry, electronics and electrical appliances and other fields.
Smart Images

Figure BDA0005217550130000101
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength and high-conductivity glass fiber reinforced PBT composite material and a preparation method thereof, belonging to the technical field of polymer material processing and modification. Background Art
[0002] Polybutylene terephthalate (PBT) is a high-performance engineering plastic. Its symmetrical molecular structure gives it high crystallinity and good mechanical properties. PBT also has good heat resistance, excellent electrical properties and high chemical resistance. In addition, PBT parts are easy to flow and mold during processing, and the molding cycle is short, which can reduce production costs. Based on the above advantages, polybutylene terephthalate (PBT) resin is widely used in the automotive industry, electronic appliances, packaging, mechanical equipment and other fields. However, since the tensile strength, flexural strength and flexural modulus of pure PBT resin are all low, the scope of application in the industrial field is subject to certain restrictions. Therefore, it needs to be modified to further improve the mechanical properties. Adding glass fiber to PBT resin can further improve the tensile strength, flexural strength, flexural modulus and notched impact strength of PBT resin while maintaining its original advantages, thereby broadening the scope of application of PBT resin.
[0003] With the advancement of science and technology and the development of industry, many fields have put forward higher requirements for plastic materials. For example, some parts in the field of new energy automobile manufacturing, including millimeter wave radar brackets, sensor plugs, etc., require materials to have strong electrical conductivity while having high mechanical properties to meet the anti-interference and anti-static design requirements of automobile parts; in addition, in the fields of electronic appliances, electronic packaging and industrial manufacturing, high strength, high heat resistance and high conductivity are also required for the engineering plastic materials involved. The way to give plastic materials conductive properties is mainly to add various conductive fillers or conductive polymers, such as conductive carbon black, graphite, carbon fiber, metal powder, metal fiber and multi-walled carbon nanotubes, etc. However, traditional conductive fillers have a high addition ratio, which will have an adverse effect on the original mechanical properties and processing properties of the material. Therefore, in order to obtain high-strength and high-conductivity glass fiber reinforced PBT composite materials, it is necessary to select more efficient conductive fillers and optimize the formulation system. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength, high-conductivity glass fiber reinforced PBT composite material and a preparation method thereof, so as to solve the deficiencies of the prior art.
[0005] The technical solution of the present invention is as follows:
[0006] A high-strength, high-conductivity glass fiber reinforced PBT composite material, prepared from the following raw materials by weight percentage:
[0007] Polybutylene terephthalate (PBT) resin 40-90%,
[0008] Chopped glass fiber 5-30%,
[0009] Carbon nanostructured material CNS 0.1~10%,
[0010] Dispersing aid 0.1~10%,
[0011] Toughening agent 0.1~15%,
[0012] Antioxidant 0.1~5%,
[0013] Other additives 0-2%.
[0014] The polybutylene terephthalate (PBT) resin has a melt index of more than 15 g / 10 min and a density of 1.28 to 1.32 g / cm3 under the test conditions of 250° C. and 2.16 kg.
[0015] The chopped glass fibers have a length of 3 mm, a fiber diameter of 10 μm, a moisture content of ≤0.05%, and the surface of the glass fibers is modified by a silane-type active agent.
[0016] The carbon nanostructured material CNS is a multi-walled carbon nanotube material with a unique bifurcated structure and distributed in an array. Different from the traditional multi-walled carbon nanotube (CNT), it has a unique branch structure and better dispersibility.
[0017] The dispersing aid is one or more of pentaerythritol stearate, polyethylene wax, silicone, and vinyl bisstearamide.
[0018] The toughening agent is one or more of glycidyl methacrylate grafted ethylene-methyl acrylate copolymer, glycidyl methacrylate grafted ethylene-butyl acrylate copolymer, glycidyl methacrylate grafted ethylene-octene copolymer, methyl methacrylate-butadiene-styrene copolymer, and ethylene-methyl acrylate copolymer.
[0019] The antioxidant comprises a main antioxidant and an auxiliary antioxidant, wherein the main antioxidant is a hindered phenol antioxidant; and the auxiliary antioxidant is a phosphite or ester antioxidant.
[0020] The main antioxidant is one or more of 3,5-di-tert-butyl-4-hydroxybenzyl diethyl phosphate (3114), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (1010), and 2,β-(3,5-di-tert-butyl-4-carboxyphenyl) propionate octadecyl ester (1076); the auxiliary antioxidant is one or more of triphenyl phosphite (TPP), tris(2,4-di-tert-butylphenyl) phosphite (168), and bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite (626).
[0021] The high-strength, high-conductivity glass fiber reinforced PBT composite material comprises the following steps:
[0022] (1) Weigh polybutylene terephthalate (PBT) resin, carbon nanostructured material CNS, dispersing aid, toughening agent, antioxidant and other additives according to the above proportions, and mix them in a high-speed mixer for 2 to 5 minutes.
[0023] (2) Weigh chopped glass fibers according to the above ratio.
[0024] (3) adding the uniform mixture in step (1) to the main feeder of the twin-screw extruder, and adding the corresponding chopped glass fibers in step (2) to the side feeder, and after the main feed material is melted, melt-blending and extruding granulation with the material at the side feed port, the temperature of each section of the extruder is as follows: 90-100° C. in zone 1, 150-160° C. in zone 2, 230-240° C. in zone 3, 230-240° C. in zone 4, 230-240° C. in zone 5, 235-245° C. in zone 6, 230-245° C. in zone 7, 230-240° C. in zone 8, 230-240° C. in zone 9, 235-245° C. in zone 10, and the main engine speed is 400-500 rpm.
[0025] The present invention enhances the dispersibility of CNS in PBT resin by adding a novel carbon nanostructured material CNS and a suitable dispersing aid, thereby giving the glass fiber reinforced PBT resin higher electrical conductivity while further improving its tensile strength, flexural strength and flexural modulus. DETAILED DESCRIPTION
[0026] The present invention can be further described by the following preferred embodiments, but these embodiments are only for illustration and do not limit the scope of the present invention.
[0027] The main raw materials used in the examples and comparative examples of the present invention are as follows:
[0028] Polybutylene terephthalate (PBT) resin: TH6100, Xinjiang Blue Mountain Tunhe Polyester Co., Ltd.;
[0029] Chopped glass fiber: ECS303H, Chongqing International Composite Materials Co., Ltd.
[0030] Carbon Nanostructured Materials CNS: ATHLOS TM CNS, Cabot;
[0031] Dispersing aid: pentaerythritol stearate (PETS), Oshada Chemical;
[0032] Toughening agent: PTW, Dow, USA;
[0033] Primary antioxidant: 1010, BASF, Germany;
[0034] Auxiliary antioxidant: 168, BASF, Germany;
[0035] Carbon black: m800, Cabot.
[0036] Example 1
[0037] 75.5 parts of polybutylene terephthalate (PBT) resin TH6100, 2 parts of toughening agent PTW, 0.5 parts of dispersing aid PETS, 1 part of carbon nanostructured material CNS, 0.1 parts of primary antioxidant 1010, 0.4 parts of auxiliary antioxidant 168 and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS303H were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded and granulated to obtain a conductive glass fiber reinforced PBT composite material.
[0038] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 230-240°C, zone 4 230-240°C, zone 5 235-245°C, zone 6 235-245°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-240°C, zone 10 235-245°C, and the main engine speed is 400-500rpm.
[0039] Example 2
[0040] 74.5 parts of polybutylene terephthalate (PBT) resin TH6100, 2 parts of toughening agent PTW, 0.5 parts of dispersing aid PETS, 2 parts of carbon nanostructured material CNS, 0.1 parts of primary antioxidant 1010, 0.4 parts of auxiliary antioxidant 168 and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS303H were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded and granulated to obtain a conductive glass fiber reinforced PBT composite material.
[0041] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 230-240°C, zone 4 230-240°C, zone 5 235-245°C, zone 6 235-245°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-240°C, zone 10 235-245°C, and the main engine speed is 400-500rpm.
[0042] Example 3
[0043] 73.5 parts of polybutylene terephthalate (PBT) resin TH6100, 2 parts of toughening agent PTW, 0.5 parts of dispersing aid PETS, 3 parts of carbon nanostructured material CNS, 0.1 parts of primary antioxidant 1010, 0.4 parts of auxiliary antioxidant 168 and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS303H were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded and granulated to obtain a conductive glass fiber reinforced PBT composite material.
[0044] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 230-240°C, zone 4 230-240°C, zone 5 235-245°C, zone 6 235-245°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-240°C, zone 10 235-245°C, and the main engine speed is 400-500rpm.
[0045] Example 4
[0046] 65.5 parts of polybutylene terephthalate (PBT) resin TH6100, 2 parts of toughening agent PTW, 0.5 parts of dispersing aid PETS, 1 part of carbon nanostructured material CNS, 0.1 parts of primary antioxidant 1010, 0.4 parts of auxiliary antioxidant 168 and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 30 parts of short-cut glass fiber ECS303H were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded into granules to obtain a conductive glass fiber reinforced PBT composite material.
[0047] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 230-240°C, zone 4 230-240°C, zone 5 235-245°C, zone 6 235-245°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-240°C, zone 10 235-245°C, and the main engine speed is 400-500rpm.
[0048] Example 5
[0049] 64.5 parts of polybutylene terephthalate (PBT) resin TH6100, 2 parts of toughening agent PTW, 0.5 parts of dispersing aid PETS, 2 parts of carbon nanostructured material CNS, 0.1 parts of primary antioxidant 1010, 0.4 parts of auxiliary antioxidant 168 and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2-5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 30 parts of short-cut glass fiber ECS303H were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded into granules to obtain a conductive glass fiber reinforced PBT composite material.
[0050] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 230-240°C, zone 4 230-240°C, zone 5 235-245°C, zone 6 235-245°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-240°C, zone 10 235-245°C, and the main engine speed is 400-500rpm.
[0051] Example 6
[0052] 63.5 parts of polybutylene terephthalate (PBT) resin TH6100, 2 parts of toughening agent PTW, 0.5 parts of dispersing aid PETS, 3 parts of carbon nanostructured material CNS, 0.1 parts of primary antioxidant 1010, 0.4 parts of auxiliary antioxidant 168 and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 30 parts of short-cut glass fiber ECS303H were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded and granulated to obtain a conductive glass fiber reinforced PBT composite material.
[0053] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 230-240°C, zone 4 230-240°C, zone 5 235-245°C, zone 6 235-245°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-240°C, zone 10 235-245°C, and the main engine speed is 400-500rpm.
[0054] Comparative Example 1
[0055] 76.5 parts of polybutylene terephthalate (PBT) resin TH6100, 2 parts of toughening agent PTW, 0.5 parts of dispersing aid PETS, 0.1 parts of primary antioxidant 1010, 0.4 parts of auxiliary antioxidant 168 and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2-5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS303H were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded into granules to obtain a glass fiber reinforced PBT composite material.
[0056] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 230-240°C, zone 4 230-240°C, zone 5 235-245°C, zone 6 235-245°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-240°C, zone 10 235-245°C, and the main engine speed is 400-500rpm.
[0057] Comparative Example 2
[0058] 66.5 parts of polybutylene terephthalate (PBT) resin TH6100, 2 parts of toughening agent PTW, 0.5 parts of dispersing aid PETS, 0.1 parts of primary antioxidant 1010, 0.4 parts of auxiliary antioxidant 168 and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2-5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 30 parts of short-cut glass fiber ECS303H were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded into granules to obtain a glass fiber reinforced PBT composite material.
[0059] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 230-240°C, zone 4 230-240°C, zone 5 235-245°C, zone 6 235-245°C, zone 7 230-240°C, zone 8 230-240°C, zone 9 230-240°C, zone 10 235-245°C, and the main engine speed is 400-500rpm.
[0060] Performance evaluation and implementation standards:
[0061] In the above embodiments and comparative examples, the performance of the products was tested according to the following standards and conditions.
[0062] The apparent density is tested according to ISO 1183-1; the flexural strength and flexural modulus are tested according to ISO 178, the sample size is 80×10×4mm, the bending speed is 2mm / min, and the span is 64mm; the tensile strength is tested according to ISO 527, the sample is type 1A, and the tensile speed is 5mm / min; the simply supported beam notched impact strength is tested according to ISO 179-1, the sample size is 80×10×4mm, the A-type notch is selected, and the test temperature is 23℃; the surface resistivity is tested according to ASTM D257.
[0063] The test results of various physical properties of the products obtained in Examples 1 to 6 and Comparative Examples 1 to 2 are listed in Table 1.
[0064] By comparing Examples 1 to 3 with Comparative Example 1 and Examples 4 to 6 with Comparative Example 2, it can be seen that adding a small amount of carbon nanostructured material CNS can give PBT resin excellent electrical conductivity. As the CNS content increases, the surface resistivity of the PBT composite material gradually decreases and the electrical conductivity gradually increases. It is also found that adding carbon nanostructured material CNS can improve the tensile strength, flexural strength and flexural modulus of the PBT composite material. The greater the amount of CNS added, the greater the improvement, while the notched impact strength remains basically unchanged.
[0065] The present invention obtains a high-strength, high-conductivity glass fiber reinforced PBT composite material, which not only has excellent conductivity, but also has improved tensile strength, flexural strength and flexural modulus to a certain extent, and can be used in the automotive industry, electronic appliances, electronic packaging and other fields.
[0066] Table 1 Physical property test results of embodiments and comparative examples
[0067]
[0068] The above embodiments are for better illustrating the specific contents of the present invention, but the protection scope of the present invention is not limited thereto. Any researcher familiar with the technical field can easily change or replace these embodiments, and apply the basic principles of the present invention to other embodiments without creative work. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.
Claims
1. A high-strength, high-conductivity glass fiber reinforced PBT composite material, characterized in that: It is prepared from the following raw materials in percentage by weight: Polybutylene terephthalate (PBT) resin 40-90%, Chopped glass fiber 5-30%, Carbon nanostructured material CNS 0.1~10%, Dispersing aid 0.1~10%, Toughening agent 0.1~15%, Antioxidant 0.1~5%, Other additives 0-2%.
2. The high-strength, high-conductivity glass fiber reinforced PBT composite material according to claim 1, characterized in that: The polybutylene terephthalate (PBT) resin has a melt index of more than 15 g / 10 min and a density of 1.28 to 1.32 g / cm3 under the test conditions of 250° C. and 2.16 kg.
3. The high-strength, high-conductivity glass fiber reinforced PBT composite material according to claim 1, characterized in that: The chopped glass fibers have a length of 3 mm, a fiber diameter of 10 μm, a moisture content of ≤0.05%, and the surface of the glass fibers is modified by a silane-type active agent.
4. The high-strength, high-conductivity glass fiber reinforced PBT composite material according to claim 1, characterized in that: The carbon nanostructured material CNS is a multi-walled carbon nanotube material with a unique bifurcated structure and distributed in an array. Different from the traditional multi-walled carbon nanotube (CNT), it has a unique branch structure and better dispersibility.
5. The high-strength, high-conductivity glass fiber reinforced PBT composite material according to claim 1, characterized in that: The dispersing aid is one or more of pentaerythritol stearate, polyethylene wax, silicone, and vinyl bisstearamide.
6. The high-strength, high-conductivity glass fiber reinforced PBT composite material according to claim 1, characterized in that: The toughening agent is one or more of glycidyl methacrylate grafted ethylene-methyl acrylate copolymer, glycidyl methacrylate grafted ethylene-butyl acrylate copolymer, glycidyl methacrylate grafted ethylene-octene copolymer, methyl methacrylate-butadiene-styrene copolymer, and ethylene-methyl acrylate copolymer.
7. The high-strength, high-conductivity glass fiber reinforced PBT composite material according to claim 1, characterized in that: The antioxidant comprises a main antioxidant and an auxiliary antioxidant, wherein the main antioxidant is a hindered phenol antioxidant; and the auxiliary antioxidant is a phosphite or ester antioxidant.
8. The high-strength, high-conductivity glass fiber reinforced PBT composite material according to claim 7, characterized in that: The main antioxidant is one or more of 3,5-di-tert-butyl-4-hydroxybenzyl diethyl phosphate (3114), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (1010), and 2,β-(3,5-di-tert-butyl-4-carboxyphenyl) propionate octadecyl ester (1076); the auxiliary antioxidant is one or more of triphenyl phosphite (TPP), tris(2,4-di-tert-butylphenyl) phosphite (168), and bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite (626).
9. A method for preparing the high-strength, high-conductivity glass fiber reinforced PBT composite material according to any one of claims 1 to 8, characterized in that: The steps are as follows: (1) Weigh polybutylene terephthalate (PBT) resin, carbon nanostructured material CNS, dispersing aid, toughening agent, antioxidant and other additives according to the ratio described in claim 1, and mix them in a high-speed mixer for 2 to 5 minutes; (2) weighing chopped glass fibers according to the ratio described in claim 1; (3) adding the uniform mixture in step (1) to the main feeder of the twin-screw extruder, and adding the corresponding chopped glass fibers in step (2) to the side feeder, and after the main feed material is melted, melt-blending and extruding granulation with the material at the side feed port, the temperature of each section of the extruder is as follows: 90-100° C. in zone 1, 150-160° C. in zone 2, 230-240° C. in zone 3, 230-240° C. in zone 4, 230-240° C. in zone 5, 235-245° C. in zone 6, 230-245° C. in zone 7, 230-240° C. in zone 8, 230-240° C. in zone 9, 235-245° C. in zone 10, and the main engine speed is 400-500 rpm.
Citation Information
Patent Citations
Carbon nanostructure composite and preparation method thereof
CN105502330A
PBT (Polybutylene Terephthalate) composite and preparation method thereof
CN109306157A
Polybutylene terephthalate compositions and articles
CN117295784A
High performance polymer compositions containing carbon nanostructures
CN118871522A
Cited By
High-conductivity and high-thermal-conductivity PBT composite material and preparation method thereof
CN121673774A